PHYSICAL ACTIVITY AND THE IMMUNE SYSTEM – A BRIEF REVIEW (University Arena, 2025)
Background. Physical activity is an essential element in maintaining optimal health. Studies on this topic shows that the physical condition of the body can influence the evolution of a disease, such as viral infections. Very recent research supports the idea that regular exercise could be effective in prevention and could reduce the risk of severe lung complications, including the disease of 2020 - Covid 19. (Yan, Z., Spaulding, H.,2020). Social distancing measures taken to control the current COVID-19 pandemic have led to limited physical activity options. Many people are in quarantine or self-isolation at home. However, this should not lead us to adopt a sedentary lifestyle, which is associated with decreased immunity. Studies suggest that the prolonged intense exercise causes immunosuppression, whereas moderate-intensity exercise improves immune function and potentially reduces risk and severity of respiratory viral infections. (Martin, S., Pence, B., Woods, J., 2009).Objectives. We propose a brief overview of the current global phenomenon, the pandemic Corona virus, which affects the quality of life of people around the world and how it can be combated with physical activity.Purpose: In the context of the novel coronavirus outbreak, that question has gained urgency and also, thanks to recent research, emergent answers. The purpose of this work is to highlight the influence of physical activity on the immune system. The latest science suggests that being fit boosts our immune systems, and that even a single workout can amplify and improve our ability to fight off germs (Nieman, D., Wentz, L., 2019).Conclusion. Exercise has a profound effect on the normal functioning of the immune system. It is generally accepted that prolonged periods of intensive exercise training can depress immunity, while regular moderate intensity exercise is beneficial.